PENGARUH PEMBERIAN HORMON 2,4-D (DIKLORO FENOKSIASETAT) DAN BAP (BENZYL AMINO PURIN) TERHADAP PERTUMBUHAN KALUS JERUK KUOK (Citrus nobilis Lour) SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI DI SMA - Lesmanawati, Sri Eggi; Mahadi, Imam; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to determine the effect of the hormone combination with 2,4-D and BAP on callus growth Jeruk kuok (Citrus nobilis Lour) and to generate learning module design in senior high school biology. This study used a Factorial Completely Randomized Design from 5 x 4 with three replications. The first factor of 2,4-D (D) consists of 5 levels: 0 mgL-1, 1 mgL-1, 2 mgL-1, 3 mgL-1, and 4 mgL-1. The second factor of BAP (B) consists of levels: 0 mgL-1, 1 mgL-1, 2 mgL-1, and 3 mgL-1. The parameters measured were the time appeared callus, percentage of callus, callus width and texture of the callus. Data were analyzed using ANAVA and tested further with DMRT at 5% level. The results showed that the effect of 2,4-D and BAP significantly influenced the growth of Jeruk Kuok. The combination of 2,4-D and BAP showed the fastest callus in treatment of D4B2 compared to treatment D0B0. The combination of 2,4-D and BAP indicated that 8 treatments had a 100% live percentage value of D3B0, D3B1, D3B2, D3B3, D4B0, D4B1, D4B2, and D4B3. The combination of 2,4-D and BAP shows the highest rate of callus width at D3B2 treatment. The combination of 2,4-D and BAP shows the best callus texture on the treatment of D2B3, D3B0, D3B1, and D3B2. The best treatment of the combination of 2,4-D and BAP hormones is in the treatment of D2B3 to produce embryogenic callus so that it can be used for cell suspension cultures. The results of this study can be used as the design of learning resources in the form of modules in the concept of modern biotechnology high school class XII.Keywords: 2,4-D, BAP, Callus cultures, Module